Air Resistivity Model Of Jute Needled Nonwoven. Issue 15 (23rd November 2022) - Datta, Mallika; Chatterjee, Biswapati; Ray, Prabir; Das, Srijan; Nath, Devarun
ABSTRACT: This research work focuses on the measurement of the air resistivity property of jute nonwoven through a simple approach. The Box-Behnken design of experiment (DOE) involved 15 jute nonwovens to study the influence of process parameters of needle nonwoven machine such as areal density (g/m 2 ), punch density, and depth of needle penetration. In addition to that, the airflow resistivity of 15 jute nonwovens was measured and compared with values obtained by various analytical models found in the literatures. It was observed that the diameter of coarser jute fiber (average diameter, 60 µm) was in the range of viscous boundary length at 135 Hz sound energy. A modified empirical model was developed for determining air resistivity of the jute nonwoven directly from the areal density, punch density, and depth of penetration. The SEM study showed that the polygonal cross-section of multicellular jute fiber was responsible for the higher air drag/barrier, which leads to a higher magnitude of the coefficient of bulk density in the 'new jute model.' Finally, the newly developed air resistivity model for jute nonwoven offered an indirect method of conferring a numerical value to the surface characteristics of fibers. The modified empirical model developed for determining the air resistivity was validated through 18 new jute nonwovens with mean absolute percentage error as low as 7.0%.